2010
DOI: 10.3832/ifor0549-003
|View full text |Cite
|
Sign up to set email alerts
|

Fine root production and distribution in the tropical rainforests of south-western Cameroon: effects of soil type and selective logging

Abstract: © iForest -Biogeosciences and Forestry IntroductionThe tropical rainforests of southern Cameroon as African rainforests are subjected to deforestation due to shifting cultivation, commercial timber and forest exploitation (Archard et al. 2002). This is stimulated by demographic and economic crisis forces. To counteract this process, the Cameroonian government has decided to develop, through the Tropenbos Cameroon Programme (TCP), methods and strategies for sustainable management of his rainforests (Foahom & J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…Often, studies that have compared fine-root biomass and architectural and morphological traits in other tropical regions (Table S1) have revealed contrasting dominance of root traits in forests at different recovery stages. Contrary to our findings, comparative studies in the tropics have usually reported higher total fine-root biomass in old growth (unlogged) forests than in logged forests (Hopkins et al 1996, Leuschner et al 2009, Ibrahima et al 2010, Barbhuiya et al 2012, Gautam & Mandal 2012. However, in broad-leaved evergreen subtropical forests in southeast China, Lin et al (2015) reported higher total fine-root (diam.…”
Section: Resultscontrasting
confidence: 92%
See 2 more Smart Citations
“…Often, studies that have compared fine-root biomass and architectural and morphological traits in other tropical regions (Table S1) have revealed contrasting dominance of root traits in forests at different recovery stages. Contrary to our findings, comparative studies in the tropics have usually reported higher total fine-root biomass in old growth (unlogged) forests than in logged forests (Hopkins et al 1996, Leuschner et al 2009, Ibrahima et al 2010, Barbhuiya et al 2012, Gautam & Mandal 2012. However, in broad-leaved evergreen subtropical forests in southeast China, Lin et al (2015) reported higher total fine-root (diam.…”
Section: Resultscontrasting
confidence: 92%
“…, Ibrahima et al . , Barbhuiya et al . , Gautam & Mandal ) and a few fine‐root architectural and morphological traits (Hopkins et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this requirement, most of the past studies in tropical forests are found to be limited to analyzing the aboveground systems (Chave et al 2008;Djomo et al 2011;Malhi et al 2011;Doughty et al 2013;Ngo et al 2013;Girardin et al 2014;Malhi et al 2014) and only a few studies concern to the belowground aspects (Ibrahima et al 2010;Powers and Perez-Aviles 2013;Noguchi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The West African forest belt is a biodiversity hotspot and a provider of fundamental ecosystem services, now degraded and reduced to a patchwork of forest fragments (CEPF 2003). Selective logging is possibly the primary cause of degradation in African forests with recognized impacts on carbon stocks (Cazzolla Gatti et al 2015, Hawthorne et al 2012) and fine root production (Ibrahima et al 2010). In Ghana, concessions interest more than half of the reserves (Hawthorne & Abu-Juam 1995).…”
Section: Introductionmentioning
confidence: 99%